Sustainable spectrophotometric determination of dextromethorphan and bupropion: A fourier self-deconvolution approach - Fotouh R. Mansour; Samar H. Elagamy; Omar M. Elserwi; Amira H. Kamal (Green Analytical Chemistry)
A novel, simple, cheap, environment-friendly and accurate chemometric method using Fourier self-deconvolution has been developed for the simultaneous determination of dextromethorphan (DXM) and bupropion (BUP) in their newly approved tablet dosage form using distilled water as a solvent. Direct UV/Vis spectrophotometry could not be employed for determination of both drugs in their mixture due to the significant spectral overlap. FSD is a powerful computational technique extensively used in signal processing. It traditionally combines deconvolution and curve fitting, where deconvolution first identifies the number and positions of distinguishable peaks in the mixture spectrum. The deconvoluted spectra of each drug were utilized for determination of DXM and BUP at points where there is no spectral interference from the other drug. Processing of spectral data was conducted using OriginPro 2024b software. The proposed method was validated according to ICH guidelines. The method was applied for determination of each drug in synthetic laboratory mixture prepared as the composition of their formulated tablet. The results of the proposed method were compared to those of the reported HPLC one. The greenness of the method was assessed using analytical Eco-scale, MoGAPI, and AGREE. The scores for the developed method and reported one were (94 and 87), (84 and 70), (0.78 and 0.54) using Eco-scale, MoGAPI, and AGREE, respectively. It was proven that the developed method is ecofriendly. The whiteness profile of the developed method was also assessed in comparison with the reported HPLC method, based on the principles of White Analytical Chemistry (WAC) using the WAC calculator. The developed UV method achieved a whiteness score of 84.1 %, outperforming the reported HPLC method, which had a score of 68.5 %.